Illicit City-Making and Its Materialities. Introduction to the Special Issue. Issue 3 (21st December 2022) - Müller, Frank I.; Weegels, Julienne
Provoked by Charles Tilly's analogy of state-making as organized crime (1985 ), this issue aims at better understanding the material conditions of illicit city-making – that is, of urbanization and criminal governance, as well as the criminalizing discourses and strategies that underpin them. In opposition to the liberalist paradigm of states vs. illegitimate enemies, Tilly proposed to see the dynamics of state-making (and the negotiation of protection and extraction involved therein) as akin to the dynamics of organized crime. After all, both seek to establish territorial sovereignty based on their capacity to monopolize violence. More importantly, this analogy illuminates the way in which states can enact their protection rackets without a pre-established legitimate authority. Bringing this analogy to the urban realm – seeing city-making as continuously imbricated in attempts to foster the legitimacy of heterogeneously authored protection rackets – this special issue elicits the practices, flows, extraction, and actors involved in illicit city-making, as well as the processes that deem them so.